Health and social needs of asylum seekers and Ukrainian refugees in Lithuania: A mixed-method protocol - El Arab, Rabie Adel; Urbanavice, Rita; Jakavonyte-Akstiniene, Agne; Skvarcevskaja, Marija; Austys, Donatas; Mateos, Jose Tomas; Briones-Vozmediano, Erica; Rubinat-Arnaldo, Esther; Istomina, Natalja (Frontiers in Public Health, 2023)
Refugees, asylum seekers, and migrants often do not end up in the places they expected. Because of the pandemic impacts, their exposure to COVID-19 may be increased as a result of crowded camps and detention centers. A total of 4537 undocumented migrants entered Lithuania via Belarus from June 2021 to November 30, 2022. In the period 24 February 2022 to 30 November 2022, Lithuania's Immigration Department registered 71,386 Ukrainian refugees. This study investigates the healthcare and social needs of recent asylum seekers who have crossed the Belarusian border and Ukrainian refugees in Lithuania. This is a study protocol for a mixed-methods study which will involve qualitative interviews with asylum seekers who crossed from Belarus in June 2021 and Ukrainian refugees. During a quantitative phase, refugees and asylum seekers will be asked to complete questionnaires. In this study, validated questionnaires will be used, including the Hopkins Symptom Checklist (HSCL-25), the Harvard Trauma Questionnaire (HTQ), and the Short Form 36 (SF-36). Participants will also be asked to self-report sociodemographic information. As a result of the findings of this study, it is possible to provide guidelines for improving access to health care services, including prevention (i.e., vaccination programs) and treatment of chronic and acute illnesses, through primary and secondary healthcare delivery, thereby reducing negative health outcomes. This study may shed light on the social needs of asylum seekers and refugees in Lithuania. In addition, this may provide insight into how they are integrating into the community, such as what their employment and educational prospects are.